HUKUM DAN DIPLOMASI LOKAL SEBAGAI WUJUD PEMECAHAN MASALAH DI WILAYAH PERBATASAN KALIMANTAN DAN MALAYSIA - Jawahir Thontowi (Yuridika, 2015)
Border area disputes generally arise because of differences in views of the boundary line between a country over the borders located on the map enclosed in an international agreement. Claims of a country over territories that protrude the sovereignty of other countries, are often the cause of the dispute because of a new fact-based new agreement. Principles of application of posidetis juris may arise because of differences in delimitation understanding, the determination of demarcation, other geographic and political factors (border management), which are also factors causing disputes. This study is regarding the international and national laws to govern and manage borders territory by using method of inquiry primary legal sources and empirical data from Kalimantan. This research concludes the following results. The first result is that there are rules of international and national laws governing borders territory, but it is not sufficient to settle the complex of problem in border areas. The second results is that the local government has been involved in various types of local diplomacy by using mediation performed by local adat, both in privates and public cases. In order to improve ability to cope such problems, it is important to provide capacity buildings which are enable local government and local adat apparatuses to make a better problem legal solving.